‘Don’t Crunch My Credit’: Member State Governments’ Preferences on Bank Capital Requirements - Sébastien Commain (Politics and Governance, 2021)
Across Europe, banks remain, to this day, the main suppliers of finance to the European economy, but also a source of systemic risk. As such, regulating them requires that policymakers find an appropriate balance between restricting their risk-taking behaviour and increasing lending to support economic growth. However, the ‘varieties of financial capitalism’ that characterize national banking sectors in Europe mean that the adoption of harmonised capital requirements has different effects across countries, depending on the country-specific institutional setting through which banks provide lending to the national economy. This article conducts a new analysis of Member State governments’ positions in the post-financial crisis reform of the EU capital requirements legislation, expanding the scope of previous studies on the topic. Here, I examine in detail the positions of Member States on a wider set of issues and for a broader set of countries than the existing literature. Building on the varieties of financial capitalism approach, I explain these positions with regard to structural features of national banking sectors. I find that Member State governments’ positions reveal a general agreement with the proposed increase of bank capital requirements, while seeking targeted exemptions and preferential treatment that they deem necessary to preserve their domestic supply of retail credit.